Evaluating a credit guarantee agency in a developing economy: A non-parametric approach - Ong, Hway Boon; Habibullah, Muzafar Shah; Radam, Alias; Mohamed, Azali (2003)
Banks are important sources of external credit but they are reluctant to lend to small and medium enterprises (SMEs) due to the high credit risk involved. Therefore, Credit Guarantee Corporation (Malaysia) Limited (CGC) was set up to assist SMEs to secure loans from financial institutions in Malaysia. Being the sole issuer of credit guarantees to SMEs, the performance of CGC directly reflects the availability of credit guarantees to SMEs. Hence, to ascertain the accessibility of credit guarantees, this study evaluates the efficiency of credit guarantee schemes provided by CGC From a non-parametric analysis, CGC is found to be operating at a relatively low level of overall technical efficiency. Therefore, CGC should consider reallocating its existing inputs as well as increase the amount of credit guarantees granted to SMEs in order to achieve a reasonable level of efficiency.